Can Pure Thalamic Strokes Lead to Severe Impairment of Arousal? - Jaakkola, Elina; Likitalo, Olli; Niinivirta‐Joutsa, Katri; Joutsa, Juho (Wiley, 2025)
Background: The thalamus has been considered critical for maintaining consciousness, but it is not clear if thalamic strokes can lead to severe impairment of arousal. The aim of this study was to investigate whether thalamic damage alone is sufficient to cause severe impairment of arousal in stroke patients.
Methods: Patients with new-onset ischemic stroke without mass effect, leading to severe impairment of arousal, were identified retrospectively from the electronic medical records of patients treated 2004-2019 at Turku University Hospital. In addition, 500 stroke patients without impairment of arousal were included as controls.
Results: We identified nine patients with coma or stupor following an acute stroke involving the thalamus. Five of these patients remitted following endovascular therapies but had residual lesions intersecting the thalamus. In the four patients with long-term coma or stupor, the thalamic lesions extended into the brainstem and overlapped in regions considered part of the reticular formation. These brainstem regions were specific for patients with long-term coma or stupor, as none of the five patients who remitted following endovascular therapy or 500 control stroke patients (including 39 patients with stroke lesions intersecting the thalamus) had lesions intersecting these regions.
Conclusions: These results demonstrate that thalamic strokes without extension into the brainstem are not sufficient to cause severe impairment of arousal.